Transfer of Land Rights Due to Inheritance - Anggriani, Reni; Yuniarlin, Prihati; Isniyati, Qodriyah; Fauziah, Nafiza (Universitas Muhammadiyah Magelang, 2025)
The transfer of ownership of land due to inheritance is a form of transfer of rights regulated in Law Number 5 of 1960 concerning the Basic Regulation of Agrarian Principles (UUPA). The transfer of Land Rights is carried out through Land Registration, which is regulated in Government Regulation Number 24 of 1997 concerning Land Registration. Juridically, when the owner of the land dies, then in the interest of the law, the title to the land passes to the heirs. In practice, this process often raises problems, because there has been no transfer to the heirs, who are constrained by the determination of heirs, and the completeness and validity of the proof documents as heirs are proven by the Certificate of Inheritance (SKW) or Court Determination. This research uses a normative juridical method with a legislative approach. The results of the study show that the main obstacle in the transfer of rights due to inheritance comes from the lack of public understanding of the administrative procedures of inheritance and the transition process in Agrarian and Spatial Planning/National Land Agency (ATR/BPN) of the National Land. The absence of this transition process has caused problems among the heirs, so it is necessary to transfer rights for the sake of legal certainty.